Sistem Pendidikan Pondok Pesantren Dalam Meningkatkan Life Skills Santri Pondok Di Pesantren Bustanul Ulum Al- Ghozali Desa Dukuh Dempok Kecamatan Wuluhan Kabupaten Jember - Sari, Firda; Anam, Khoirul (Pendidikan Islam Pascasarjana IAIN Jember, 2025)
This study aims to describe and analyze the Islamic boarding school education system in improving the life skills of students at the Bustamul Ulum Al-Ghozali Islamic boarding school in Dukuh Dempok Village, Wuluhan, Jember. This study uses a qualitative approach, field research type. Data collection techniques use in-depth interviews, non- participant observation, and documentation studies. The collected data are interpreted and analyzed using the process of data condensation, data presentation and conclusion drawing. The technique of testing the credibility of the data uses triangulation of sources, techniques and time. Problems: 1) The education system of the Bustanul Ulum Al-Ghazali Islamic Boarding School in Dukuh Dempok Village, Wuluhan District that supports the implementation of Life Skills education. 2) Life Skills education integrated into curricular and extracurricular programs at the Bustanul Ulum Al-Ghazali Islamic boarding school in Dukuh Dempok Village, Wuluhan District, Jember Regency. 3) The implications or involvement of an Islamic boarding school education system in the implementation of Life Skills education programs at the Bustanul Ulum Al-Ghozali Islamic Boarding School in Dukuh Dempok Village, Wuluhan District, Jember Regency.